Apakah Karakter Eksekutif, Kepemilikan Institusional dan Kualitas Audit Mempengaruhi Penghindaran Pajak ? - Widjaja, Albert; Hananto, Hari; Girindratama, Muhammad Wisnu (Universitas Teuku Umar, 2024)
This research aims to assess whether executive characteristics, institutional ownership, and audit quality influence tax avoidance in manufacturing industry sector companies listed on the IDX for the 2018-2022 period. The research method used is quantitative. The variable used is the dependent variable consisting of tax avoidance. Meanwhile, the independent variables include executive character, institutional ownership, and audit quality. Control variables consist of firm size and leverage. The population of this research is all companies listed on the BEI in 2018-2022. Sampling is based on specific criteria using a non-probability sampling method with a purposive sampling technique. The sample criteria are completeness of the 2018-2022 financial reports, completeness of research variable data, and inclusion in the audited financial reports of the big four KAP companies. This research data analysis uses the SPSS application with multiple linear regression techniques. The results of the findings are that executive character has a positive effect on tax avoidance in manufacturing companies listed on the IDX. Institutional ownership has a negative effect on tax avoidance in manufacturing companies listed on the IDX. Audit quality has a negative effect on tax avoidance in manufacturing companies listed on the IDX.